Effective Math Instruction : Shifting to Meet Today's Standards. - Dupree, Jared (Professional Resources Ser., 2016)
Adequately address the shifts in mathematics instruction to meet the demands of the Common Core and other new state standards with this comprehensive guide. Teachers will be empowered to build lessons, templates, and exemplars for practical application.